Plasma concentration-time profile of a single dose of enteric-coated omeprazole in male and female healthy volunteers - GÖREN, MEHMET ZAFER; AKIN, ŞEHNAZ; GÜLHAN, REZZAN; ONAT, FİLİZ (My University, 2000)
O b je c tiv e : T h e b io a vaila b ility of a single dose (20 m g) o f tw o e n te ric -c o a te d o m e p ra z o le fo rm u la tio n s, m arketed in T urkey, given 10-15 m in b e fo re b reakfast, w as studied in 12 healthy vo lu n te e rs (6 m ales and 6 fem ales) in a d o u b le blind, cro s s o v e r design. M e th o d s : B lood sam ples w ere collected prior to and at 10 tim e points w ithin 12 hrs. after dosing. P la s m a o m e p ra z o le c o n c e n tra tio n s w e re m easured by H P LC te ch n iq u e in our laboratory. R e s u lts a n d C o n c lu s io n s : T he tw o products w ere found to be b io e q u iva le n t in term s of extent of a b s o rp tio n (th e a re a u n d e r the p la s m a c o n c e n tra tio n -tim e cu rve s). M u ltip e a k p la sm a co n ce n tra tio n pro file s w e re seen in m ost of the su b je cts w ith both products. T im e to the e a rlie r peaks w as 1-2 hrs. and those peaks w ere low er in a m p litu d e th a n th e p e a ks re a ch e d a p p ro x im a te ly 4 .5 hrs. a fte r the a p p lica tio n . In te re stin g ly, the m u ltip e a k profile w as m ore fre q u e n t and the e a rlie r peaks w ere sig nificantly higher in fe m a le su b je cts than in m ales. The reason fo r th is g e n d e r d iffe re n ce in m ultipeak p la s m a c o n c e n tra tio n - tim e p ro file of oral o m e p ra zo le needs fu rth e r investigation.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Bioavailability; Coated capsules; Enteric; Gender difference; Omeprazole; Omeprazole; Bioavailability; Enteric; coated capsules; Gender difference